2009
DOI: 10.1002/ijc.24878
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of human homologs of yeast MOB1

Abstract: MOB (Mps One Binder) is a conserved gene family found in all major kingdoms.The MOB genes are essential components acting in mitotic exit and cytokinesis in both budding and fission yeasts. They are further identified as tumor suppressors in Drosophila (D.) melanogaster. Recently, they are found to be involved in the emerging Drosophila Hippo-LATS tumor suppressor pathway. Seven human homologs of yeast MOB (hMOB1A, 1B, 2A, 2B,3,4,5) have been discovered. The hMOB1B is the gene that has been extensively studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 88 publications
(252 reference statements)
0
43
0
1
Order By: Relevance
“…In particular, although many upstream activators of LATS, such as Hippo/MST and Mats/MOB1, have been reported (20)(21)(22), direct negative regulators of LATS are yet to be identified. In this study, we have provided convincing evidence that Itch E3 ubiquitin ligase is a bona fide binding partner and negative regulator of LATS1.…”
Section: T7-r1(d505v)-yfp 35s:plc2-cfpmentioning
confidence: 99%
“…In particular, although many upstream activators of LATS, such as Hippo/MST and Mats/MOB1, have been reported (20)(21)(22), direct negative regulators of LATS are yet to be identified. In this study, we have provided convincing evidence that Itch E3 ubiquitin ligase is a bona fide binding partner and negative regulator of LATS1.…”
Section: T7-r1(d505v)-yfp 35s:plc2-cfpmentioning
confidence: 99%
“…The activation of Mst1/2 leads to phosphorylation and activation of their direct substrates, Lats1/2 (Chan et al, 2005). Mob1, which forms a complex with Lats1/2 (Chow et al, 2010), is also phosphorylated and activated by Mst1/2, resulting in enhanced interaction between Lats1/2 and Mob1 (Hirabayashi et al, 2008;Praskova et al, 2008). Similar to that in Drosophila, MST1/2/Sav1 and Lats1/2/Mob1 form a physical and functional core of the Hippo pathway.…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 95%
“…37 As further evidence, in a recent paper, Chow et al confirmed that membrane-targeted activation of LATS1 by MOB1 significantly increases LATS1 kinase activity toward its substrate YAP. 42 Although from these studies it is clear that LATS1 kinase activity can be enhanced by membrane-targeting, it is not yet known if this is the only mechanism of LATS1 activation or if the same holds true for LATS2. In addition, since these studies only use ectopic expression of targeted proteins, it would be important to establish the dynamics of endogenous LATS in response to MOB1 expression.…”
Section: Biochemical Function As Ser/thr Kinasementioning
confidence: 99%